P2-S2.11 Focused and early intervention in rural areas can impact on HIV transmission in Southern India. (10th July 2011) - Washington, R; Bhattacharjee, P
Abstract : Background: A number of districts in Karnataka, south India have an equal prevalence of HIV in rural and urban areas. A link worker scheme focused on prevention interventions with rural female sex workers, was implemented under the USAID supported Samastha project (2006–2011). Methods: A rapid rural mapping covering 7700 villages across eight districts helped map 16 043 rural female sex workers clustered in about 1700 villages. Rural female sex workers (RFSW) were defined as women who lived and practiced sex work within the village. Peer educators supervised by outreach link workers identified, educated, directly provided condoms and mobilised RFSW to reach HIV services. STI and counselling and testing services were integrated into Primary Health Centres. An individualised web based management information system tracked outreach and services. Polling booth surveys were used to measure key behavioural outcomes. Results: By the fourth year of implementation, 14 697 (91.6%) of the estimated RFSW were reached. Monthly contact rates were sustained at 85%, with each RFSW directly receiving a mean of 28.3 condoms per month. Condom use rates rapidly increased to 63% at last sex with any partner and 78% with clients. 81% received STI services and more than 67% had been directly referred and received their HIV status. The proportion reporting with STI symptoms remained stable at around 60%; however, 64% of these were vaginal discharge. Genital ulcer rates decreased from 5.5 to 0.8% and other STI conditions from 6.1 to 1.7%. HIV prevalence among RFSW across districts ranged from 2 to 4%. Overall, HIV prevalence among antenatal women declined from 1.9 to 0.5% (2006–2009) in these districts. Conclusions: Focused and early interventions can reduce HIV transmission in rural areas and could be impacting even at the population level. It would be important to sustain focused prevention interventions in rural India.